Examining Role of Self-Control Exertion in the Strength Model of Self-Control Using Modified Versions of the Sequential Task Paradigm - Lee, Nick (Curtin University, 2018)
Current study examines the role of effort on the ego-depletion effect in a sequential-task experimental paradigm as employed by the strength model of self-control. Evidence from three studies, including one meta-analysis and two laboratory experiments, indicates that conventional approaches of measuring self-control exertion is inadequate for testing the strength model. Furthermore, attempts to employ monetary incentives and task duration similarly did not have any significant effect on the ego-depletion effect.